Effectiveness of a resilience school-based intervention in adolescents at risk: a cluster-randomized controlled trial - Llistosella, Maria; Castellví, Pere; García-Ortiz, Mercedes; López-Hita, Griselda; Torné, Clara; Ortiz, Ramona; Guallart, Erika; Uña-Solbas, Estefanía; Carlos Martín-Sánchez, Juan (Frontiers in Psychology, 2024)
Introduction School offers a key context to promote resilience. The aim of this study was to assess the effectiveness of a school-based resilience intervention in 578 at-risk adolescents aged 12 to 15, emphasizing the significance of resilience improving mental health. Methods A cluster-randomized controlled trial with parallel arms was conducted during the 2021/22 academic course. A specific training of six 55-minute sessions over 6 weeks was carried out for the students. Each session consisted of 5 minutes of mindfulness, followed by 45 minutes of the corresponding activity: introduction to resilience, self-esteem, emotional regulation strategies, social skills, problem solving, community resources, and peer support. Primary outcomes were assessed by the Child Youth Resilience Measure-32 at baseline (T1), post-intervention (T2), and then at the 24-week follow-up (T3). Both groups were compared using the Student’s t-test. The effect size was calculated using Cohen’s d and linear regression models were used. Results A total of 578 adolescents were included, 323 in the control group and 255 in the intervention group. Significant differences in both crude and adjusted analyses for Child Youth Resilience Measure were observed at 24 weeks follow-up, showing higher resilience for the intervention group [IG, M = 128.7, SD = 14.2; CG, M = 125.3, SD = 18.4; p = 0.027; d = 0.2; p = 0.043, d = 0.16]. Furthermore, in Depressive symptoms, lower values were found for the intervention group in both crude and adjusted analyses [IG, M = 2.3 (SD = 2.5); CG, M = 2.8 (SD = 2.5); p = 0.04; d = −0.20; p = 0.037, d = −0.18]. Discussion This study contributes to fostering resilience and positive adolescent development. It also reinforces the potential of multicomponent interventions. More continuous follow-up assessments are needed to identify possible long-term changes in resilience. Clinical Trial Registration Identifier: NCT05133115. https://clinicaltrials.gov/study/NCT05133115.